2018
DOI: 10.1016/j.aller.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori seropositivity protects against childhood asthma and inversely correlates to its clinical and functional severity

Abstract: Helicobacter pylori seropositivity protects against childhood asthma and inversely correlates to its clinical and functional severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
2
19
1
5
Order By: Relevance
“…This supports data from a smaller case‐control study showing a nonsignificant lower H. pylori positivity among children with allergies compared with individuals without allergies: 13.9% (17/122) vs 22.4% (22/98), respectively . In contrast, 2 other case‐control studies showed a significantly lower seroprevalence of H. pylori among allergic children compared with individuals without allergies: 25.6% (23/90) vs 44.4% (40/90) and 20% (36/180) vs 60% (108/180), respectively . In addition, the latter study also demonstrated significantly higher serum IL‐10 levels in nonatopic subjects …”
Section: Clinical Manifestationssupporting
confidence: 85%
See 1 more Smart Citation
“…This supports data from a smaller case‐control study showing a nonsignificant lower H. pylori positivity among children with allergies compared with individuals without allergies: 13.9% (17/122) vs 22.4% (22/98), respectively . In contrast, 2 other case‐control studies showed a significantly lower seroprevalence of H. pylori among allergic children compared with individuals without allergies: 25.6% (23/90) vs 44.4% (40/90) and 20% (36/180) vs 60% (108/180), respectively . In addition, the latter study also demonstrated significantly higher serum IL‐10 levels in nonatopic subjects …”
Section: Clinical Manifestationssupporting
confidence: 85%
“…Kato et al 11 15 and 20% (36/180) vs 60% (108/180), respectively. 16 In addition, the latter study also demonstrated significantly higher serum IL-10 levels in nonatopic subjects.…”
Section: Iron Deficiency Anemiamentioning
confidence: 94%
“…Farelerde yapılan bir çalışmada ise H. pylori'nin iki antijeninin (γ-glutamyl transpeptidase ve VacA) Treg hücreleri uyardığı gösterildi (29). Çok yeni yayınlanan bir çalışmada H. pylori seropozitivitesi astımlı çocuklarda atopik olmayan sağlam çocuklardan anlamlı olarak düşük bulunmuş ve astımın ağırlığı ile de negatif korelasyon göstermiştir (21). Yine ülkemizden bir yeni çalışmada da non-atopik çocuklarda H. pylori seropozitivitesi ve IL-10 düzeyleri yüksek bulunmuştur (17).…”
Section: Discussionunclassified
“…Daha sonra yapılan çalışmalarda hijyen hipotezinin biyolojik temelleri desteklenmiş; çocukluk çağı enfeksiyonlarının T helper (Th) 1 yanıtı artırdığı ve atopi gelişiminde önemli olan Th2 yanıtı baskıladığı gösterilmiştir (7)(8)(9)(10)(11). Hipotezin ilk ortaya atıldığı andan itibaren virüs (9,10,(12)(13)(14)(15)(16), bakteri (2,7,9,10,13,17) ya da parazit (3,(8)(9)(10)(11)13) olmak üzere çeşitli çocukluk çağı enfeksiyonları ile atopi arasındaki ilişki araştırılmış; lehte ve aleyhte birçok sonuçla tartışmaya günümüzde de devam edilmiştir (2,(17)(18)(19)(20)(21).…”
unclassified
“…Similarly, Karakullukcu et al studied the protective role of H. pylori neutrophil‐activating protein on childhood asthma by analyzing its prevalence in both asthmatic and healthy children, showing a higher prevalence in males . From an epidemiologic point of view, Fouda et al, who studied 90 asthmatic children and 90 healthy controls, reported a significantly lower prevalence of H. pylori in the first group (25.6% vs 44.4%) and an inverse correlation between asthma and anti‐ H. pylori IgG titers . Similar results were reported by Taye et al, who enrolled 856 Ethiopian children in their study, showing an inverse relationship between H. pylori infection, CagA positivity, and both atopy and allergic asthma .…”
Section: Respiratory Diseasesmentioning
confidence: 55%